Phytochemical evaluation, isolation and quantification of amino acid from the leaves of sauropus androgynus linn. by HPTLC method - V.E.IDA CHRISTI,; M.ABINAYA,; T.UMA POORANI,; S.MOHAN, (International Journal of Pharma and Bio Sciences, 2019)
The plant Sauropus androgynus belongs to the family Euphorbiaceae is a very important medicine as well as good nutrient. To explore the nutritional value of this plant is necessary.Our aim is to identify and estimate some of the nutrients especially the essential aminoacids present in the plant. In traditional system of medicine, the plant is known to possess various therapeutic values like antioxidant, anti diabetic, anti pyretic, antiseptic, anti hypertensive and also used to treat various ophthalmic diseases. It is also consumed as a vegetable by human being as it contains more number of primary and secondary nutrients in it. In this study, the physiochemical parameters like ash values, extractive values, total fibre content were determined then, the presence of important phytoconstituents and aminoacids were confirmed by the preliminary phytochemical study. The total phenol, flavonoid and vitamin C contents were estimated by spectral methods. The particular amino acids were identified by Thin Layer Chromatography and Paper chromatographic methods and few of the amino acids were quantitatively estimated by HPTLC method. In this present work by preliminary phytochemical study, it reveals that the plant possess some phytochemicals such as carbohydrates, alkaloids, tannins, phenols, flavonoids, vitamin C and amino acids. There are eight amino acids were identified by paper chromatography among which Glycine, Cysteine, Aspartic acid and Leucine were quantified by HPTLC method and also these amino acids were quantitatively estimated by colorimetricaly. Future studies can be followed to the structural elucidation of the isolated compounds. And also plan for new nutraceutical formulation.